Pemodelan Redaman Hujan Sebagai Parameter Power Link Budjet Pada Base Transceiver Station (BTS) Jaringan 5G : Modeling Rain Attenuation as a Budjet Power Link Parameter in 5G Network Base Transceiver Station (BTS) - Made Sutha yadnya; I Wayan Sudiarta; I Putu Gede Wirarama Wedashwara (JURNAL SAINS TEKNOLOGI & LINGKUNGAN, 2023)
Rain is a natural phenomenon that occurs in tropical climates during the period it occurs which is a nuisance in wireless communications. The research focus for 5G communications is ongoing to be able to overcome or mitigate rainy conditions. Rain data from satellite images is taken in the form of processed images with different color degradation. The resulting rainfall data is then converted into rain attenuation. This rain attenuation is used to predict noise interference from rain so that it can be overcome in rainy conditions. Statistical data from rain attenuation was modeled and generated numerically using ARMA which was modified to ARIMA so that observations from non-stationary to stationary. The ARIMA model value in this research is ARIMA (6,1,6).